Corporate valuation around the world: The effects of governance, growth, and openness - Chua, Choong Tze (Institutional Knowledge at Singapore Management University, 2010)
The purpose of this paper is to provide a comprehensive analysis of corporate valuation around the world. Specifically, we (i) document and compare corporate valuation around the world, and (ii) identify the key factors that drive cross-country differences in valuation. In doing so, we utilize the country-level Tobin's q (CTQ), computed as the ratio of the aggregate market value to book value of all assets held by all public firms domiciled in a country, which amounts to the Tobin's q for the [`]market portfolio' of the country. The key findings of the paper are: First, CTQ varies greatly across countries, ranging from 0.73 for Venezuela to 2.11 for Finland, with the international mean of 1.30 during our sample period 1999-2004. Despite the steady integration of the world economy in recent years, corporate valuation remains starkly different across countries. Second, apart from the effect of corporate governance, cross-country differences in corporate valuation are significantly driven by the growth options of countries represented by the R&D intensities, capital expenditures, and GDP growth. In addition, the degree of capital market openness has a significant, independent effect on valuation. Third, our regression analyses show that CTQ varies directly with shareholder rights, enforcement of insider trading laws, GDP growth, R&D intensity, and the degree of capital market openness. The key findings remain robust to the inclusion of inflation and industry effects.